Assessment of RC Bridges integrity by means of low-cost investigations - Flavio Stochino; MariaLuisa Fadda; Fausto Mistretta (Fracture and Structural Integrity)
Infrastructure aging is an important problem nowadays, in particular for countries like Italy in which the main motorways were built 50 years ago. Huge budgets are necessary to keep infrastructure and bridges in service. In addition, the lack of a proper and timely maintenance, entails an increase of the deterioration and therefore higher costs of repair. Thus, the need of methods capable of assessing the reliability of the infrastructure in the frame of Bridge Management System (BMS), is patent. The aim of this work is to provide a robust decision-support tool for the analysis of the data collected with field inspection. The innovative aspect of the proposal is the introduction of two factors which take into account the location of the damage, and the mechanical characterization of the material in the definition of a Condition Rating Number (CRN). The analysis of an existing Reinforced Concrete (RC) bridge network is presented in order to show the accuracy of this new method